INCIDÊNCIA DE PÉS PLANOS E NORMAL EM CRIANÇAS EM IDADE ESCOLAR (7 A 11 ANOS) NA ZONA RURAL E URBANA. - VIEIRA NUNES, LEANDRO AUGUSTO; PEREIRA BARBOSA, ALEXANDRE BARROS (Brazilian Journal of Surgery & Clinical Research)
Objective: Check the incidence of flat feet in students from rural and urban areas between the age group 7-11years in both genders. Methods: - to collect data, stating name, age, weight, height, place of residence urban or rural area, scaling a sample of 120 young people, using systematic sampling closing an error margin of 5%. The data collected were grouped into a table where the percentage were made; 60 rural and 60 urban areas. Result: There are plans standing predominance in urban school children compared to rural. These results confirm the mechanism of supporters atrophy muscles of plantar abóbadas individual walking shoes constantly. It was found that most of the children were asymptomatic. Conclusion: There was a higher incidence of flat feet in the urban area and there was high rate of podais changes, highlighting the need for preventive measures.